Digital Literacy Transformation of Learners with Special Needs through TPACK Approach in IPAS Learning in Elementary School - Renanda Ajeng Pramusti; Bahrul Ulum; Maharani Putri Kumalasani (Universitas Negeri Padang, 2024)
Students with special needs, such as slow learners and dyslexia, experience challenges in filtering valid information. With this, digital literacy in slow learners and dyslexic students through the TPACK approach is a solution to this problem. This study aims to analyze the transformation of digital literacy of slow learners and dyslexic students through the TPACK approach in IPAS subjects, especially social studies. This research uses descriptive qualitative methods with data collection techniques: observation, interviews, and documentation. The results showed that the digital literacy of slow learners and dyslexic students increased significantly through interactive map technology, e-comic, and Google Classroom in social studies subjects. The results of this research are expected to contribute to developing more effective and inclusive technology. This research can also be a reference for educators using the TPACK approach to improve digital literacy.